EFEKTIVITAS MENCUCI LUKA MENGGUNAKAN DAUN SIRIH HIJAU (Piper Batle Linn) TERHADAP PENYEMBUHAN DIABETIC FOOT ULCER - Silvia Hernitasari; Dina Alfiana Ikhwani (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
Diabetic Foot Ulcer is a common and worrying complication of diabetes mellitus, often caused by ineffective treatment, which can lead to amputation or death. This study used a Quasi Experimental research design with a Pre PostTest Group Design approach. The sampling technique for this study was Probability Sampling with a Simple Random Sampling approach. The sample in this study was 34 respondents consisting of 17 respondents with intervention group I, 17 respondents as intervention group II. The comparison before and after washing the wound using green betel leaves with the Wilcoxon test obtained a p-value of 0.001 (≤0.05) which means H0 is rejected and H1 is accepted indicating that there is an effect between washing the wound using green betel leaves on the healing of Diabetic Foot Ulcer. The comparison before and after washing the wound using normal saline with the Wilcoxon test obtained a p-value of 0.001 (≤0.05) which means H0 is rejected and H1 is accepted indicating that there is an effect between washing the wound using normal saline (NaCl) on the healing of Diabetic Foot Ulcer. Comparison of wound washing in intervention group I and intervention group II using Mann-Whitney test analysis showed a p-value of 0.708 (≥0.05) so H0 was accepted and H1 was rejected, which means there was no significant comparison of healing Diabetic Foot Ulcer between washing wounds using green betel leaves and washing wounds using normal saline.Washing wounds using green betel leaves and normal saline can affect the healing of Diabetic Foot Ulcer effectively, so green betel leaves can be an alternative in carrying out wound care for Diabetic Foot Ulcer.